Effect of lemongrass oil (Cymbopogon sp.) as anesthesia material in the closed transportation process of white snapper seeds (Lates calcarifer) - Tristiana Yuniarti; Alfabetian Harjuno Condro Haditomo; Janet Rizkiana (Depik, 2022)
White snapper, Lates calcalifer, is a sea fish who was widely cultivated because the price reaches IDR 63,000.00/ kg for market size (500 gram up). Demand of white snapper on the market tends to increase, but there are high mortality problems when transporting seeds from seed sources to the destination location where was relatively far away. Lemongrass oil had geraniol compounds, citronellol and aromatherapy odors could reduce anxiety (sedatives) and reduce the level of fish metabolism by making the fish faint. The purpose of this study was to determine the effect of lemongrass oil on survival rate, blood profile (total of erythrocytes, leukocytes, and glucose levels) post-transportation of white snapper seeds with length and weight average of 9.71 ± 0.62 cm and 11.33 ± 1.82 g, respectively. The method used was experimental and completely randomized design (CRD) with 4 treatments 3 replications (0, 10, 20, 30 µl/L). The results showed that the allocation lemongrass oil with different concentrations gave a real effect on the survival rate but did not significantly affect the blood profile after transportation. The best concentration of lemongrass oil is 10 µl/L with survival rate of 100%.Keywords:AnesthesiaWhite snapperCymbopogon sp.Transportation